Nutritional Analisis Status Gizi Dengan Prestasi Belajar Pada Siswa Di SDN Mawar 8 Kota Banjarmasin - Abdullah Abdullah; Norfai Norfai (Jurnal Kesehatan Indonesia, 2019)
Nutritional status is one of the factors that can affect learning achievement. School-age children who are malnourished will cause children to become weak, tired and sick, so children are often absent and have difficulty following and understanding the lesson. Nutritional conditions will also affect children's ability to understand lessons in school and influence learning achievement. This research is an analytical survey with a cross sectional approach. The population in this study was all students from grade 1 to grade 4 in Banjarmasin SDN Mawar 8 in 2018 totaling 83 students. The sample size was 69 respondents with cluster sampling technique. Nutritional status data were obtained using the Body Mass Index (BMI) by age (BMI/U), ie children aged 5-18 years by performing high measurements and using microtoice and weight measurements using digital scales and recording data types and age data in full years and months. . Learning achievement data is obtained based on the value of the last report card. Data were analyzed using univariate and bivariate Che Square tests using computer programs with a confidence level of 95%. Statistically there is a significant relationship between nutritional status and learning prestige in Banjarmasin SDN Mawar 8 with p-value (0.014) < Î± (0.05). Based on the results of the study, it was suggested the need for cooperation from the school with parents of students in terms of providing a healthy and nutritious breakfast and lunch, while also conducting further research studies on the most basic causes using a case control approach and multivariate testing for knowing the dominant causal factors for student achievement.